KONDISI SOSIAL EKONOMI MASYARAKAT SEKITAR HUTAN DI DESA TANGAI JAYA KECAMATAN MENTEBAH KABUPATEN KAPUAS HULU - Linoria, Rose Merry Melawati; Dewantara, Iswan; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2016)
The community uses forest products as a source of livelihood to improve socio-economic conditions by participating in the use of local natural resources. The aim of this study is to reveal the income of the people around the forest and uncover the level of welfare of the people in Tangai Jaya Village of Mentebah Subdistric in Kapuas Hulu Regency. This study used surveys through interviews with a questionnaire guide. Samples were taken using simple random sampling with the number of respondents as many as 70 households. The data collected were the descriptive analyzed processed by adding up all income derived from both farming and non farming activities and then measured using the indicators of Regional Minimum Wage of Kapuas Hulu and analyzing the level of social welfare in accordance with BKKBN. The results showed that the total income of the community around the forest in Tangai Jaya village ranged from IDR 100,000/month to IDR 30,500,000/month with an average total income of IDR 2,235,857/month. The level of welfare in Tangai Jaya Village with 98.67% or 69 household is categorized as Family Welfare Phase I and 1.43% or 1 categorized as Family Welfare Phase III. There are 30 households in Padang Jaya hamlet and 39 households in Sungai Tekuyung Hamlet that are categorized as Family Welfare Phase I. Meanwhile, 1 household of Sungai Tekuyung hamlet is categorized as Family Welfare Phase III. Keywords: Socio-economic conditions, income, level of welfare, Tangai Jaya Village.